Singing for themselves : essays on women in popular music - Rudden, Patricia Spence (Cambridge Scholars, 2007)
Singing for Themselves: Essays on Women in Popular Music is a fresh look at a topic that has attracted increasing interest in recent years. In this collection, scholars from a number of disciplines look at various artists and movements and come to some ne.